2021
DOI: 10.1099/mgen.0.000649
|View full text |Cite
|
Sign up to set email alerts
|

The genomes of nucleocytoplasmic large DNA viruses: viral evolution writ large

Abstract: The nucleocytoplasmic large DNA viruses (NCLDVs) are a diverse group that currently contain the largest known virions and genomes, also called giant viruses. The first giant virus was isolated and described nearly 20 years ago. Their genome sizes were larger than for any other known virus at the time and it contained a number of genes that had not been previously described in any virus. The origin and evolution of these unusually complex viruses has been puzzling, and various mechanisms have been put forward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 106 publications
(253 reference statements)
2
25
2
Order By: Relevance
“…This suggests common ancestors for the corresponding viral and eukaryotic moieties at an “early” proto-eukaryotic stage of evolution, a hypothesis supported by the large Marseilleviridae topoisomerase II proteins of nearly 1200 amino acids, which similarly branch as sister to all eukaryotic topoisomerase II proteins to the exclusion of the homologous archaeal gyrases [ 28 ]. This branching is also consistent with several studies finding that the origin of NCLDVs predates the divergence of modern eukaryotes [ 13 , 21 , 88 , 89 ], and with the high conservation rate of NCLDV core genes in Marseilleviridae [ 76 , 77 ]. In either the “early” or “late” scenarios, divergence from eukaryotic or proto-eukaryotic histones may have been driven by the need to distinguish viral histones from host histones in cellular location, properties, and functions.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests common ancestors for the corresponding viral and eukaryotic moieties at an “early” proto-eukaryotic stage of evolution, a hypothesis supported by the large Marseilleviridae topoisomerase II proteins of nearly 1200 amino acids, which similarly branch as sister to all eukaryotic topoisomerase II proteins to the exclusion of the homologous archaeal gyrases [ 28 ]. This branching is also consistent with several studies finding that the origin of NCLDVs predates the divergence of modern eukaryotes [ 13 , 21 , 88 , 89 ], and with the high conservation rate of NCLDV core genes in Marseilleviridae [ 76 , 77 ]. In either the “early” or “late” scenarios, divergence from eukaryotic or proto-eukaryotic histones may have been driven by the need to distinguish viral histones from host histones in cellular location, properties, and functions.…”
Section: Introductionsupporting
confidence: 91%
“…Since then more than 60 marseilleviruses have been identified on five continents from water, soil, sewage, invertebrates, and humans through genomic and metagenomic sequencing [ 75 ]. Marseilleviruses have circular genomes of ~ 340–390 kb that encode 22–25 of the 26 most common NCLDV core genes and many genes specific to Marseilleviridae [ 76 , 77 ]. A study in melbournevirus found that the capsids contain a large and dense body near the capsid internal membrane of a density suggestive of nucleoprotein complex [ 78 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3a). Moreover, genes largely conserved across the Nucleocytoviricota (despite multiple independent deletions rendered only one gene strictly conserved in all viruses 24 ) and used for the phylogenetic reconstruction of the phylum are essential for pandoravirus replication (Fig. 3d).…”
mentioning
confidence: 99%
“…3d). These genes include: B DNA Polymerase (PolB), A32-like packaging ATPase (A32), virus late transcription factor 3 (VLTF3), large RNA polymerase subunits (RNAP1 and RNAP2), TFIIB transcriptional factor (TFIIB) and D5-like primase-helicase 11,16,24 . This data aligns with their use for phylogenetic reconstructions by indicating their likely ancestry for the phylum.…”
mentioning
confidence: 99%